CHANGE MANAGEMENT VARIABLES AND ADMINISTRATIVE EFFECTIVENESS IN COVID-19 ERA AND BEYOND: A STUDY OF SCHOOL PRINCIPALS’ IN CALABAR EDUCATIONAL ZONE - Isueken, Onosetale Tracy, (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2022)
During and after the covid 19 pandemic, successful school administration depends on adapting to change and meticulously adhering to emerging rules and regulations. Based on this premise, this study was designed to investigate change management variables as predictors of administrative effectiveness in the covid-19 era and beyond. Three research questions with the corresponding hypothesis were raised to guide the study to achieve its aim. The study was conducted in the Calabar Education Zone of Cross River State using a survey research design. The samples of 87 principals 350 teachers were purposively used in the study from the population of 87 principals and 1955 teachers. Two researchers’ made instruments tagged ‘change management questionnaire’ and ‘administrative effectiveness questionnaire’ were used for data collection. The instrument’s construct validity was ascertained using factor analysis while the internal consistency of the instrument sub-scale was ascertained using Cronbach Alpha (α). The alpha α coefficient were .79, .81, .85, .87 respectively base on the instrument sub-scale. Hypotheses were tested at .05 level of significance using Simple linear regression statistical analysis. The results of the study revealed that in the covid 19 era and beyond, transformational leadership, participation and communication, innovativeness as change management variables significantly predict principals’ administrative effectiveness in the study areas. Recommendations were set based on the findings that there is a need for school principals to adapt to change, be innovative and change their administrative strategies for effective school administration during and after the covid 19 pandemic.